10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BackgroundThe relationship between acute myocardial injury and prognosis in acute myocarditis (AM) is unclear.PurposeTo evaluate myocardial injury characteristics by cardiovascular magnetic resonance (CMR) tissue parameters and their impact on adverse outcomes of AM patients.Material and MethodsThis retrospective study enrolled 41 patients with fulminant myocarditis (FM, including 17 FM patients without mechanical circulatory support [MCS] and 24 FM patients with MCS) and 35 patients with non-fulminant myocarditis (non-FM). Cine, mapping (native T1, T2, and post-T1), and late gadolinium enhancement (LGE) of the left ventricle were performed during CMR. Adverse clinical outcomes consisted of a primary endpoint, major adverse cardiovascular events (MACEs), and a secondary endpoint, a decline in functional status (defined as New York Heart Association [NYHA] functional classes II-IV).ResultsCompared with patients with non-FM, those in FM with MCS exhibited increased native T1 (P = 0.001), extracellular volume (ECV) (P = 0.018), and LGE (P = 0.005) values. After adjusting for the clinical variables (CRP > 67.9 mg/dL), LGE > 8.4% remained independently associated with adverse clinical outcomes and improved the predicting ability of the model (C-statistic improved from 0.74 to 0.82).ConclusionThe burden of necrosis and fibrosis was greatest in FM with MCS, while edema was similar across groups. Higher LGE% adds incremental prognostic value. A new classification using CRP and LGE improved prediction of adverse outcomes. Thus, CMR evaluation of myocardial injury extent offers variable information to improve risk stratification in FM.